Principle of parity in international treaties (1979 Camp David Convention between Israel and the Arab Republic of Egypt as a model) - Nakhlah, Muamar Ali Orabi (Journal of Economic, Administrative and Legal Sciences, 2022)
This research dealt with the issue of the principle of equivalence in international treaties, and it reviewed the Camp David agreement signed between Israel and the Arab Republic of Egypt in 1979 as a model for those treaties that involve inequality in contractual positions between its two parties, and an imbalance in privileges and obligations.The researcher aimed through his research to clarify the concept of the principle of equivalence from the perspective of international law and the Vienna Convention, and an analysis of the Camp David agreement signed by the Republic of Egypt with Israel, and to indicate the extent to which the element of inequality in rights and obligations has been achieved between the parties to that treaty Egypt can terminate or amend the Camp David Accords because it is not equitable.This study used the descriptive analytical approach, and through this approach, the researcher described the unequal treaties in terms of their nature, concept, content, images and mechanisms for their termination. The researcher also analyzed the Camp David Accords as a model for unequal treaties and evaluated them and highlighted the inequalities in them.At the end of the research, the researcher reached a set of results, the most important of which is the peace treaty between Egypt and Israel that includes many unjust provisions against the Egyptian side, in return for privileges that the Israeli side benefited from.At the conclusion of his research, the researcher recommended the Arab Republic of Egypt to invoke the theory of changing circumstances regarding the Camp David Agreement; In order to abolish it or amend its provisions in line with the Egyptian security interests.
Keywords: International treaties; Camp David; Egypt; Israel; parity; Convention